2007
DOI: 10.1007/s11284-007-0418-4
|View full text |Cite
|
Sign up to set email alerts
|

Selection of breeding territory by little bustard (Tetrax tetrax) males in Central Spain: the role of arthropod availability

Abstract: The influence of arthropod availability on the formation of male little bustard breeding territories in central Spain was studied in two consecutive years. Arthropods (68,217 individuals) were sampled using pitfall trapping and male territories estimated by means of kernel functions. Hymenopterans (ants), beetles, mites and spiders were the main taxa found in the samples, while the highest contributions in terms of biomass came from hymenopterans, beetles and orthopterans. The only group that exhibited signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
2
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 36 publications
1
31
2
4
Order By: Relevance
“…Little Bustard males benefited from the restrictions in vegetation height but not in vegetation cover provided by Shredding, probably due to their conflicting needs of visibility for displaying and courtship, and significant cover of short green plants for feeding (Morales et al, ). Agricultural practices did not affect LB male occurrence through food availability despite its known preferences for food‐rich territories to afford the costs of mating activities (Faria, Rabaça, & Morales, ; Traba, Morales, García dela Morena, Delgado, & Krištín, ). This finding may be reasonable for this species, because unploughed FFs and moderate management (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Little Bustard males benefited from the restrictions in vegetation height but not in vegetation cover provided by Shredding, probably due to their conflicting needs of visibility for displaying and courtship, and significant cover of short green plants for feeding (Morales et al, ). Agricultural practices did not affect LB male occurrence through food availability despite its known preferences for food‐rich territories to afford the costs of mating activities (Faria, Rabaça, & Morales, ; Traba, Morales, García dela Morena, Delgado, & Krištín, ). This finding may be reasonable for this species, because unploughed FFs and moderate management (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Arthropod species, mainly Orthoptera, are known to be the main part of Lesser Kestrel's diet during the post-fledging period (Franco and Andrada 1977;Tejero et al 1982;authors unpublished data). Many studies have shown that higher diversity and abundance of arthropods are associated with these habitats in the farmed landscape not only during summer (e.g., Tellería 1988;Henderson et al 2000a) but also during other seasons (e.g., breeding season, Rodríguez et al 2006;Traba et al 2008). Moreover, these habitats presumably are suitable for foraging because they have short vegetation (Henderson et al 2000b;Rodríguez et al 2006, authors, unpublished data) providing good prey accessibility (García et al 2006;Rodríguez et al 2006, authors, unpublished data), and hunting areas (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Fallow has been proved to be a preferred habitat for foraging in other farmland birds during summer (Henderson et al 2000a;Henderson et al 2000b), including many endangered species [e.g., Great Bustard Otis tarda (Moreira et al 2004), Little Bustard Tetrax tetrax, and Black-bellied Sandgrouse Pterocles orientalis (Delgado and Moreira 2000)]. Fallow is a particularly important habitat for farmland birds and, according to other studies, for other taxonomic groups (e.g., weed seeds, plants and invertebrates; see Henderson et al 2000a;Henderson et al 2000b;Van Buskirk and Willi 2004;Traba et al 2008), acting like reservoirs of farmland biodiversity.…”
Section: Discussionmentioning
confidence: 99%
“…Verdú et al (2000) pointed out that controlled traditional grazing in Mediterranean pseudo-steppes is an important measure to favour vegetation and arthropod diversity. The selection of lightly grazed areas may suggest an access to high-quality habitats where vegetation structure and diversity support a diverse arthropod community including favourite and profitable arthropods for the species (see Jiguet 2002;Traba et al 2008).…”
Section: Occurrence Of Little Bustard and Livestock Grazing Dynamicsmentioning
confidence: 99%